2010
DOI: 10.1021/ef900800d
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Synthesis Catalyzed by the KF/Ca−Mg−Al Hydrotalcite Base Catalyst

Abstract: A series of solid base catalysts, KF/Ca−Mg−Al hydrotalcite (KF mass ratio of 100%) with different cation ratios, were prepared and studied in this research. Effects of the cation ratio of the Ca−Mg−Al hydrotalcite and the methanol/oil molar ratios on the fatty acid methanol ester (FAME) yield of the transesterification of palm oil with methanol were investigated. The results of the transesterification reactions showed that all of these kinds of catalysts had a very high activity for the biodiesel yields, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 27 publications
4
72
0
1
Order By: Relevance
“…A lot of supports have been introduced for increasing the basicity of KF such as KF/ZnO, KF/Ca-Mg-Al, KF/ CaO-Fe 3 O 4 , KF/celite, KF/zeolite, and KF/LDH mainly applied for organic production. Although, a majority of the abovementioned solid bases are effective in organic transformations, they suffer from some drawbacks such as low basicity, use of expensive solid supports and tedious preparation steps [17][18][19][20][21][22][23][24][25] . Montmorillonite (MMT) clay having two silica tetrahedral sheets layered between one alumina octahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of supports have been introduced for increasing the basicity of KF such as KF/ZnO, KF/Ca-Mg-Al, KF/ CaO-Fe 3 O 4 , KF/celite, KF/zeolite, and KF/LDH mainly applied for organic production. Although, a majority of the abovementioned solid bases are effective in organic transformations, they suffer from some drawbacks such as low basicity, use of expensive solid supports and tedious preparation steps [17][18][19][20][21][22][23][24][25] . Montmorillonite (MMT) clay having two silica tetrahedral sheets layered between one alumina octahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the XRD could be utilized to evaluate the peak broadening with the crystallite size and the lattice strain due to the presence of dislocations in LDHs using the Williamson-Hall (W-H) analysis [22] :…”
Section: Synthesis Of Ca-mgal-ldhsmentioning
confidence: 99%
“…1 showed that the XRD patterns of Ca-MgAl LDHs with different treatment, without (HT-1) and with strirring (HT-2) treatment. As shown in Fig 1, the diffraction patternof HT-1 and HT-2 havesharp and symmetric peaks at 2θ = 11º (003); 23º(006); 33º(009) [16]and 61º(110) [22], which are the characteristics of LDH compounds. When XRD patterns were compared with JCPDS Mg-LDHs (JCPDS #890460) and Ca-LDHs (JCPDS #870493), another phase has found such as Mg(OH) 2 (JCPDS #070239), Al(OH) 3 (JCPDS #070324) and CaCO 3 (JCPDS #862334).…”
Section: Synthesis Of Ca-mgal-ldhsmentioning
confidence: 99%
“…Catalyzed by the hydrotalcite loaded with CH 3 COOK (Trakarnpruk & Porntangjitlikit, 2008), at the condition of a 30:1 methanol to oil molar ratio at 373 K for 6 h and 7 wt.% catalyst, the FAMEs content could get to 96.9 %. Gao et al studied KF loaded hydrotalcites KF/Mg-Al hydrotalcite (Gao et al, 2008), KF/Ca-Al hydrotalcite (Gao et al, 2010b) and KF/Ca-Mg-Al hydrotalcite (Gao et al, 2010a), found that different kinds and ratio of cations in LDHs leaded different catalytic activities. And they obtained a FAMEs highest yield over 99% (by KF/Ca-Mg-Al hydrotalcite) in 10 mins in the transesterification reaction between palm oil and methanol at 65 °C.…”
Section: Solid Base I Metal Oxidesmentioning
confidence: 99%